2022
DOI: 10.3390/ijerph19095339
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia as a Therapeutic Tool to Improve Health Parameters in Older Adults

Abstract: Aging is associated with metabolic alterations, and with a loss of strength, muscle and bone mass. Moderate intermittent hypoxia has been proposed as a new tool to enhance health-related function. The aim of this study was to evaluate the effect of moderate intermittent hypoxia exposures on parameters related to cardiovascular and bone health in older adults. A total of 38 healthy older adults (aged 65–75 years) were divided into two groups: control group (C), and hypoxia group (H) that was subjected to an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…All articles had a low risk of allocation concealment and blinding of outcomes bias. Each article was described as randomized, but the randomization method was unclear for one study [ 32 ]. Two studies revealed high risk of blinding participants and personnel bias [ 33 , 34 ], and in two other studies, the information about the blinding was unclear [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All articles had a low risk of allocation concealment and blinding of outcomes bias. Each article was described as randomized, but the randomization method was unclear for one study [ 32 ]. Two studies revealed high risk of blinding participants and personnel bias [ 33 , 34 ], and in two other studies, the information about the blinding was unclear [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each article was described as randomized, but the randomization method was unclear for one study [ 32 ]. Two studies revealed high risk of blinding participants and personnel bias [ 33 , 34 ], and in two other studies, the information about the blinding was unclear [ 32 , 35 ]. Incomplete outcome data were at a low risk of bias in all articles, except for two studies [ 35 , 36 ] that were at high risk (exclusions were not defined from the analysis and lack of several relevant statistics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies have shown that intermittent exposure to moderate hypoxia can have beneficial effects on both sick and healthy individuals (Zhang et al, 2010;Leone and Lalande, 2017;Liu et al, 2017;Wojan et al, 2021). IH is also safe and effective for the older adults, for whom short periods of alternating exposure to moderate hypoxia and normoxia environments can alter body composition and health status by improving exercise tolerance, metabolism, inflammation, and systemic arterial pressure (Burtscher et al, 2004;Timon et al, 2021Timon et al, , 2022. Studies focusing on central nervous system diseases have shown that hypoxia conditioning can promote health in the aging brain (Burtscher et al, 2021a) and make it more resistant to acute brain injury (Miller et al, 2001;Lin et al, 2003;Stowe et al, 2011Stowe et al, , 2012Wacker et al, 2012a,b), as well as play a protective role against chronic age-related neurodegenerative diseases, such as cognitive impairment (Bayer et al, 2017;Serebrovska et al, 2019c;Wang et al, 2020), Alzheimer's disease (Manukhina et al, 2016), and Parkinson's disease (Burtscher et al, 2021b).…”
Section: Intermittent Hypoxia: a Therapeutic Hypoxia Protocolmentioning
confidence: 99%
“…Previous IHT-related studies (e.g. Schega et al, 2013;Timon et al, 2021;Timon et al, 2022), have shown putative benefits for health promotion and disease prevention or treatment in elderly without elevating the mechanical stress on the musculoskeletal system. The further use of hyperoxic (fraction of inspired O 2 = 0.30-0.40) periods during IHT (termed intermittent hypoxic-hyperoxic exposure, IHHE) (Burtscher et al, 2022) appears as a safe and welltolerated method in geriatric patients (Behrendt et al, 2022), with the potential to boost transcription factors.…”
Section: Translational Knowledge From Performance To Health (And Vice...mentioning
confidence: 99%